Apis Mellifera Animal Study in a Role Perspective Using the Bibliometrix Tools (SLNA Method Application) - Ida Yayu Nurul Hizqiyah; Armansyah Putra; Meili Yanti; Unayah; Mia Nurkanti; Nia Nurdiani (Mangifera Edu, 2023)
There is no research on the study of Apis mellifera using bibliometrix tools. This study aims to determine the results of the study of Apis mellifera in a role perspective using Bibliometrix Tools. This study uses an approach that uses the Systematic Literature Network Analysis (SLNA) method assisted by bibliometrix tools in the form of four applications OpenRefine, VOSviewer, Bibliometrix, and Tableau Public. The data source used is the Scopus database. This study uses a confirmability test. Journals that publish many articles about Apis mellifera include Apidologie, Insects, and Scientific Reports. Authors who publish a lot of articles about Apis mellifera include Neumann P number 32, Chen Y and Le Conte Y number 20. The years that published a lot of articles about Apis mellifera are 2021 and 2020. The theme network consists of 5 clusters the farther the distance between topics it means that people rarely research about the topic/theme. Apis mellifera is the dominant pollinating insect that helps in the process of pollinating many plants such as blueberries and other roles, namely as medicine, from propolis to honey bee cocoons. Meanwhile, the detrimental role caused by Apis mellifera honey bees and other pollinating insects is as a vector of diseases that causes the carrying of bad bacteria that can attack plants which of course will reduce production yields.